Comparing the Effects of Training Based on Continuous Care Model and Telehealth on Quality of Sleep in Pregnant Women - Fatemeh Jalal Marvi; Masoumeh Kordi; Fariborz Rezaei Talab; Seyed Reza Mazlom (Mashhad University of Medical Sciences, 2019)
Background: Quality of sleep disorder is a common problem during pregnancy. Training based on continuous care model and telehealth has improved the quality of health care and may also ameliorate quality of sleep. Aim: The present study was conducted to compare the effects of training on the quality of sleep in pregnant women on the basis of continuous care model and telehealth. Method: This three-group clinical trial was performed in 2017 on 91 pregnant women visiting health centers in Mashhad, Iran. Orientation, sensitization, control and evaluation were carried out in the continuous care group, and four DVDs were watched by mothers in the telehealth group over the course of four weeks along with eight weeks of follow-up, and the routine care of health centers was administered for the control group. The Pittsburgh Sleep Quality Index (PSQI) questionnaire was completed at the end of weeks 8 and 12 after the start of the study. Data were analyzed in SPSS version 24 using Kruskal-Wallis statistical test. Results: The three groups were homogeneous in terms of demographic variables (P